Voice of our blood: National Socialist discourses in black metal - Olson, Benjamin (Popular Music History, 2012)
Black metal defines itself to a large degree through transgression, alienation and provocation, and in western culture, few things are more transgressive, alienating and provocative than neo-Nazism. In this article on National Socialist black metal (NSBM), the author demonstrates how certain forms of metal can be controversial and counter-cultural within the wider metal scene itself. In discursive terms, NSBM may fit in well with the pagan, Satanic and nationalist concerns of black metal, but as the author argues, “the majority of black metalers are unwilling to cross the threshold of the radical-right.” This is not necessarily because of any principled objection to racism, more because of a discomfort with the literalism and narrowness that would focus black metal’s misanthropy onto any one sub-set of humanity. NSBM’s political connotations also threaten black metal’s cherished sense of independence and individualism. The author concludes that, even if black metal’s symbolism will continue to be appropriated by the extreme right, NSBM is likely to remain a marginal phenomenon.